Land use dinamics and soil degradation in the Guabiroba catchment – Guarapuava/PR - Thomaz, Edivaldo Lopes (UFPR, 2007)
This study aims at assessing the land use dynamics as wellas its effects in physical soil characteristics and on the soildegradation in Guarapuava/PR. First of all, the landscapemapping (land unit) of Guabiroba catchment was prepared.After that, the main land use in the study area was chosen.Next, it was sought to evaluate some attributes such as landuse dynamics in subsistence agriculture, litter budget overthe soil, soil resistance, bulk density, total porosity and waterinfiltration into the soil in each land unit. Due to land usediversity and well-defined landforms, the catchment areashowed a mosaic pattern with abrupt boundary. In addiction tothis, a wide variability of soil use and physical-hydric behaviorwas observed. As a result, diverse effects on soil degradationwere found.